HPTLC fingerprint of prunus cerasoides D.Don (heartwood) extract - DR SUKHJEET KAUR GUJRAL, (International Journal of Pharma and Bio Sciences, 2019)
Prunus cerasoides D. Don commonly known as Padam or Himalayan wild cherry is a sacred plant in Hindu mythology. It is a medium sized deciduous tree. The heartwood has medicinal properties. As the global use of herbal medicinal products continue to grow, there is an increasing concern for the standardization of herbal medicines. Fingerprint analysis by HPTLC has become a potent tool for quality control of herbal medicines. It is one of the best methods for validation of complex herbal products. HPTLC as a tool was selected for the development of HPTLC fingerprints and for standardization of Prunus cerasoides D. Don (heartwood) extract. The present study was aimed to evaluate the HPTLC fingerprint profile of raw material of Prunus cerasoides D. Don (heartwood) using different extracts and this method was used for the separation of phytochemical constituents of Prunus cerasoides D. Don (heartwood) extract. HPTLC of these extracts was performed on silica gel 60F 254 by semi-automatic applicator using solvent system Methyl alcohol: Toluene: Ethyl acetate (4.0: 6.0:1.0) v/v/v. It was concluded that the established fingerprint can serve as a tool for species identification, wuthentication and quality control of herbal durgs.